The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.micpro.2008.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-range dependence and on-chip processor traffic

Abstract: Long-range dependence is a property of stochastic processes that has an important impact on network performance, especially on the buffer usage in routers. We analyze the presence of long-range dependence in on-chip processor traffic and we study the impact of long-range dependence on networks-on-chip. We propose to investigate the presence of long-range dependence in communication traces of processor ips at the cycle-accurate level. We also study the impact of long-range dependence on a real network-on-chip u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Hu et al [41] has presented a non-uniform NoC buffer space allocation algorithm under various random traffic patterns. In [42] long-range dependencies and analysis the real traffic patterns and buffer sizing problems are studied.…”
Section: Analytical Evaluation Of Dimbmentioning
confidence: 99%
“…Hu et al [41] has presented a non-uniform NoC buffer space allocation algorithm under various random traffic patterns. In [42] long-range dependencies and analysis the real traffic patterns and buffer sizing problems are studied.…”
Section: Analytical Evaluation Of Dimbmentioning
confidence: 99%
“…Usually, these topologies have to face non-uniform traffic resulting from several factors, such as routing biases, topological artifacts, long-range dependencies, traffic scenarios, and many others. Such nonuniform traffic has a vital influence on the performance of NoC topologies that have been widely studied by [19,20,95], this non-uniformity of network traffic results in local congested regions that increases network delay and lower NoC performance. The functionality of a routing method can be divided into two parts: the route computation and selection functions, as shown in fig 1 . The route computation function provides the route from the current router to the destination router FIGURE 1: The selection strategy uses network congestion information to select one direction out of directions received from routing algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of on-chip traffic [15], [16], [21] have convincingly shown that scale-invariant burstiness (i.e. self-similarity [12]) is being recognized in both pair-wised single application [21] and over entire network [16].…”
Section: Introductionmentioning
confidence: 99%
“…self-similarity [12]) is being recognized in both pair-wised single application [21] and over entire network [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation